Tidak Ada Keharmonisan sebagai Penyebab Perkara Cerai Gugat Wanita Karir di Kota Kediri - Syaefullah (MAHAKIM Journal of Islamic Family Law, 2017)
A new phenomenon that career women litigate divorce to husbands has not become taboo anymore. There are some backgrounds that cause inharmorny. A husband ideally should be good model for a wife and children. A husband has principal influences in forming harmonious family. Moreover, the main role of woman in marriage life is looking after and builds harmonious relationship to her couple. Hence, husband who has the main duty in earnings should be responsible in the accompplishment of family needs. Thus, polemical appearance will come out if above rights and duties are not accomplished, as those were happening of divorce cases in Religion Court in Kediri city on the year of 2013. The researcher does Study Analysis to the verdicts in its bearing of divorce litigation did by wives who become career women. The background of inharmonious family is because the career woman and the husband are less understand their rights and duties in marriage. Thus, if both parties understand their own responsibilities, divorce can be minimalized and a career never more becomes the cause of the inharmonious family.